2013
DOI: 10.1351/pac-rep-13-06-03
|View full text |Cite
|
Sign up to set email alerts
|

Chemical speciation of environmentally significant metals with inorganic ligands. Part 5: The Zn2+ + OH-, Cl-, CO3 2-, SO4 2-, and PO4 3- systems (IUPAC Technical Report)

Abstract: Abstract:The numerical modeling of Zn II speciation amongst the environmental inorganic ligands Cl -, OH -, CO 3 2-, SO 4 2-, and PO 4 3-requires reliable values for the relevant stability (formation) constants. This paper compiles and provides a critical review of these constants and related thermodynamic data. It recommends values of log 10 β p,q,r°v alid at I m = 0 molؒkg -1 and 25 °C (298.15 K), and reports the empirical reaction ion interaction coefficients, Δε, required to calculate log 10 β p,q,r values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(8 citation statements)
references
References 139 publications
(39 reference statements)
0
6
0
2
Order By: Relevance
“…Previous studies showed that solubility of ZnO was less than 1 mg/L at 35 °C while at 15 °C it was 3.5 mg/L 26 . At higher salinity, when released from ZnO or ZnO-NPs, Zn 2+ can form complexes with the abundant anions (e.g., Cl − and SO 4 2− ) in seawater which would reduce the concentration of free Zn 2+ ions 27 . Concentrations of dissolved zinc in the test suspension of ZnO were less than that in ZnO-NPs because ZnO has significantly larger sizes of particles (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that solubility of ZnO was less than 1 mg/L at 35 °C while at 15 °C it was 3.5 mg/L 26 . At higher salinity, when released from ZnO or ZnO-NPs, Zn 2+ can form complexes with the abundant anions (e.g., Cl − and SO 4 2− ) in seawater which would reduce the concentration of free Zn 2+ ions 27 . Concentrations of dissolved zinc in the test suspension of ZnO were less than that in ZnO-NPs because ZnO has significantly larger sizes of particles (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…At greater salinities, due to complexation of zinc ions (Zn 2+ ) with other anion present in seawater, amounts of bioavailable Zn 2+ would be less 27 . The 96-h LC50s of ZnO-NPs for the marine copepod Tigriopus japonicus were 1.22 mg/L and 2.44 mg/L at salinities of 5 and 35 ppt, respectively 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Модель Бренстеда-Гуггенгейма-Скэтчарда, получившая название «теория специфического взаимодействия» (Specific ion Interaction Theory, сокращенно SIT) и рекомендованная ИЮПАК для экстраполяции констант устойчивости комплексов на нулевую ионную силу раствора (бесконечное разбавление) [31,35,36], является наиболее простой и хорошо проработанной. Применение строгой модели К.С.…”
Section: методологияunclassified
“…Энтальпия реакции комплексообразования является функцией не только температуры, но и ионной силы раствора [29,44,35,36,118]…”
Section: корректировка логарифма константы образования по температуреunclassified
“…In speciation calculations, sorting the most feasible interactions and associations present in solutions as well as selecting their stability constants from published data can significantly affect the final predicted distribution. Several computer programs have been developed and employed to calculate the concentrations of various chemical species at equilibrium based on a database of equilibrium stability constants for inorganic species encountered in water [104]. In addition to the formation of different metal-ligand complexes, the equilibria between soluble and insoluble phases, as well as the adsorption of colloids must be considered during computational modeling.…”
Section: Tablementioning
confidence: 99%